Psychological Impact of the COVID-19 Pandemic on Frontline Health Care Physicians - Prateek Jain; Tejal Mehta; Monika Pathania (Journal of Clinical and Diagnostic Research, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic began in December 2019 in Wuhan, China. Such sudden infectious outbreaks take a toll on the psychological health of our brave frontline health care physicians. Frontline health care physicians become vulnerable to psychological problems like depression, anxiety, stress, and insomnia. Long working hours, increased patient load, and risk of spread of contagion to family members are a few of the major contributing factors. Such factors, coupled with chronic stress and emotional exhaustion predispose doctors to experience burnout which has also been reported to increase the risk of mental morbidities. Early counselling, pandemic preparedness, self-care efforts, and stress management can help to cope in these adverse times. Various online portals have also been developed as an intervention strategy in mitigating the negative impact of this pandemic. The purpose of this viewpoint is to highlight the need to address such issues in physicians, find possible root causes, and suggest relevant measures to curb the incidence of these problems.